Open-source application for real-time gait analysis using inertial sensors - Vajs, Ivan A.; Bobic, Vladislava N.; Duric-Jovicic, Milica D.; Jankovic, Milica M. (2020 28th Telecommunications Forum (TELFOR), 2020)
In this paper an open-source application for real-time gait analysis using Xsens inertial measurement units is presented. The application enables real-time data acquisition, visualization, gait segmentation, spatio-temporal parameter estimation and recording of raw and processed data. The developed algorithms are validated with an optical camera system on 8 healthy subjects. A segmentation error of 0.44±24.06 ms and a stride length root mean square error of 3.33 cm were achieved. Validated algorithms, a simple interface and an open-source implementation enable easy use of the application regardless of user's technical skills and the possibility for further research and integration with other sensor systems.